2000
DOI: 10.1091/mbc.11.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Myosin-II Tails Confer Unique Functions inSchizosaccharomyces pombe: Characterization of a Novel Myosin-II Tail

Abstract: Schizosaccharomyces pombe has two myosin-IIs, Myo2p and Myp2p, which both concentrate in the cleavage furrow during cytokinesis. We studied the phenotype of mutant myosin-II strains to examine whether these myosins have overlapping functions in the cell.myo2 + is essential.myp2 + cannot rescue loss ofmyo2 + even at elevated levels of expression.myp2 + is required under specific nutritional conditions; thus myo2 + cannot rescue under these conditions. Studies with chimeras show that the tails rather than the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
0
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 32 publications
7
55
0
5
Order By: Relevance
“…The two N-terminal motor heads bind light chains and actin filaments. The remainder of each heavy chain forms a coiled-coil tail ∼65 nm long with a 20-nm tail piece (39). The C-terminal ends of the Myo2p tails concentrated near the plasma membrane within a radius of 33 nm, a distribution indistinguishable from mEos3.2-Rng2p by KS testing (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…The two N-terminal motor heads bind light chains and actin filaments. The remainder of each heavy chain forms a coiled-coil tail ∼65 nm long with a 20-nm tail piece (39). The C-terminal ends of the Myo2p tails concentrated near the plasma membrane within a radius of 33 nm, a distribution indistinguishable from mEos3.2-Rng2p by KS testing (Fig.…”
Section: Resultsmentioning
confidence: 91%
“…Given that myo3-S469V cells did not exhibit a morphological phenotype in 1 M KCl, maintenance of the contractile ring might be the primary role of Myo3, which could be separate from its role in tolerance of high concentrations of the Cl − ion. Assuming that a signaling cascade is activated under high-Cl − ion conditions, it is possible that Myo3 provides a scaffold for signal transduction in which signaling molecules interact, as has already been speculated (Bezanilla and Pollard, 2000).…”
Section: Myo3 Cooperated With Myo2 and Cdc8 To Maintain The Actin Rinmentioning
confidence: 88%
“…A previous study has demonstrated that the recombinant Myo3 tail is monomeric because it formed an intramolecular coiled-coil and, hence, Myo3 is a single-headed myosin-II (Bezanilla and Pollard, 2000). However, contractile-ring-localized Myo3 might be in large assemblies because most of the Myo3 signal appeared as dozens of motile puncta.…”
Section: Possible Mechanisms Responsible For Myo3-mediated Maintenancmentioning
confidence: 98%
See 2 more Smart Citations